Buddhism in a muslim state: Theravada practices and religious life in Kelantan - Mohamed Yusoff Ismail, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
Although Kelantan is noted for its orthodoxy, in particular with regard to national politics and local practices of Islam, Theravada Buddhism seems to thrive very well among the local Thai ethnic group. This is testified by the fact that there are twenty temples in the state with a full-fledged Sangha organization, whose monks also serve in major towns outside the state. This paper describes some aspects of Theravada religious life in the Malay Muslim state of Kelantan, located south of Thai-Malaysian border in the east coast of the Malay Peninsula. The main concern of this paper is to examine how Thai Theravada Buddhism places itself in the context of a predominantly Malay society and adapts to local social and cultural conditions. The paper will give particular attention to the sociological and anthropological factors contributing to the non-antagonistic nature of relationship between Buddhism and Islam. Part of the answer can be traced to the historical origin of Buddhist temples in the area and also from the adaptive mechanism Theravada Buddhism has made in order to accommodate itself to the demand of the larger society in which the Thais are a minority group. In terms of its ecclesiastical organization, the Sangha body of Kelantan maintains a close link with the Thai clergy, the latter being the source of religious reference and validation. The proximity of Kelantan to Thailand also means that Buddhism in Kelantan operates within a larger religious and cultural network which transcends international political boundary.